Perancangan Mesin Hammer Millpada Aplikasi Pengolah GarriMobiledi PT. XYZ - Shalahudin Akmarullah; Kardiman (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This study presents the design of a mobile hammer mill machine for processing Garri, a popular cassava-based food product, at PT. XYZ. The objective of the research is to develop a compact and mobile solution that enables efficient Garri processing in remote locations. The design incorporates key features such as portability, robustness, and ease of operation, ensuring optimal performance and productivity. The proposed machine has the potential to enhance the Garri processing industry by providing a flexible and reliable solution for small-scale and mobile production units.The research obtained a hammer mill machine design that can be applied to the Garri processing AMMDeswith dimensions of 1157 mm x 985 mm x 850 mm and the rotating parts can be covered